On-farm seed priming to alleviate the effect of saline stress during germination of pearl millet (Pennisetum glaucum L.) (Bangladesh Journal of Botany, 2024)
Crop tolerance to salinity is of high importance particularly in the arid and semi-arid regions and pre-sowing seed treatments have been used to overcome the effect of salt stress problem. In the present experiment, on-farm primed (pearl millet seed soaked in distilled water at 25Cº in the dark for 10 hr) and dry seeds were then germinated in petri dishes under six levels of salinity (control (0), 40, 80, 120, 160 and 200 mM NaCl) under laboratory conditions. The investigation was carried out in a completely randomized design (CRD) with factorial arrangement and each treatment was replicated four times. The results showed that there were significant differences (P < 0.05) for mean germination time (MGT) and time taken for 50% germination (T50) in all salinity levels. Salinity stress decreased the seed germination traits however, on-farm priming improved it. The value of germination index (GI), seed vigor index (SVI) and germination stress index (GSI) decreased by increasing salt stress and value was recorded in case of dry seed sown as compared to primed. Results also indicated that maximum reduction in germination percentage (GP) was 12.61 and 8.57%, however; increase in T50 was 129 and 69% in dry and primed seed respectively, sown at highest level of salinity (120 mM) compared to control treatment. These findings suggest that on-farm priming is an effective method to increase seed germination grown under moderate salt stress.Bangladesh J. Bot. 53(4): 973-980, 2024 (December)